Squamous Cell Carcinoma Arising in Mature Cystic Teratoma of the Ovary - Gupta, N; Gupta, T; Jindal, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Malignant transformation of mature germ cell teratoma is rare and has been reported sporadically. Any of the constituent tissue of a teratoma has the potential to undergo malignant transformation. Squamous cell carcinoma is the most common transformation and is derived from the metaplastic squamous epithelium of teratoma. We are reporting a case of 65 years old postmenopausal women with squamous cell carcinoma arising in mature cystic cell teratoma of the ovary. DOI: http://dx.doi.org/10.3126/njog.v9i1.11191 NJOG 2014 Jan-Jun; 2(1):61-63